Legal Fundamentals of the Kazakhstan’s Environmental International Cooperation: New Vectors of Legislative Reforms - KALAGANOV, Bakhytbek; MADIYAROVA, Ainur S.; SARTAYEVA, Kaliya R.; KIM, Elina P.; APAKHAYEV, Nurlan; BURIBAYEV, Yermek A. (Journal of Environmental Management and Tourism; Vol 9 No 7 (2018): JEMT Volume IX Issues 7(31) Winter 2018DO - 10.14505//jemt.9.7(31).16, 2019)
For the last decades the international community has strengthened response to environmental challenges and signing of multilateral documents, the intensification of partnership in the environmental sphere remains one of the most effective solutions of such problems. Today we can speak about ecologization of the international cooperation and state policies which has affected the CIS countries including the Republic of Kazakhstan. At this stage of the state’s development environmental legislation of the republic can be characterized as the demonstration of immense complexity and contradictory processes, being deficient, developing quite chaotically and depending on a political climate. However, the environmental international cooperation, expansion of contractual framework and approbation of the best foreign practices are capable to transform qualitatively the Kazakhstan’s environmental legislation system and to outline new legal reformation vectors. Within the research environmental policy formation’s features of the Kazakhstan Republic in the conditions of globalization and world environmental degradation were defined; legal fundamentals of the republic’s environmental international cooperation were analyzed; influential role of Kazakhstan’s international treaties on the national environmental legislation system was characterized; legal perspectives of the Kazakhstan’s environmental legislation reformation in the context of further interstate environmental cooperation development were outlined. “The environmental international cooperation strategy of the Kazakhstan’s Republic” was recommended for the appropriate formation of the reforms’ concept development and acceptance.